Reflux episodes and esophageal impedance levels in patients with typical and atypical symptoms of gastroesophageal reflux disease - Ye, Bi Xing (Medicine (Baltimore), 2017)
To determine the relationship between baseline impedance levels and gastroesophageal reflux, we retrospectively enrolled 110 patients (54 men and 56 female; mean age, 51 ± 14 years) with suspected gastroesophageal reflux disease (GERD) who underwent 24-h multichannel intraluminal impedance and pH monitoring. Patients were stratified according to symptom (typical or atypical) and reflux types (acid reflux, nonacid reflux [NAR], or no abnormal reflux). Mean nocturnal baseline impedance (MNBI) were measured 3 cm (distal esophagus) and 17 cm (proximal esophagus) above the lower esophageal sphincter. Median distal esophageal MNBI was lower in the acid reflux group (1244 Ω; 647–1969 Ω) than in the NAR (2586 Ω; 1368–3666 Ω) or no abnormal reflux groups (3082 Ω; 2495–4472 Ω; all P < .05). Distal MNBI were negatively correlated with DeMeester score and acid exposure time. Atypical symptoms were more frequently associated with NAR than typical symptoms (P < .01). Among patients with positive symptom-association probability (SAP) for NAR, median proximal MNBI tended to be lower in patients with typical symptoms (median, 3013 Ω; IQR, 2535–3410 Ω) than in those with atypical symptoms (median, 3386 Ω; IQR, 3044–3730 Ω, P = .05). Thus, atypical GERD symptoms were more likely to be associated with NAR. The mucosal integrity of the proximal esophagus might be relatively impaired in GERD patients with typical symptoms for NAR.